تفسیر "البرھان فی حلِ مشکلات القرآن " میں مولانا عبدالسلام الرستمی ؒ کا لغوی منہج:ایک تجزیاتی جائزہ: The Lexical Method of Maulana Abdul Salam Rustami (R.A) in Tafsir Al-Burhan fi Hall Mushkilat al-Qur’an: An Analytical Review - Bilal Khan; Zakir ullah; Saqib Khan (International Research Journal of Arabic and Islamic Studies, 2024)
This research paper presents an analytical review of the lexical method employed by Maulana Abdul Salam Rustami (R.A) in his distinguished exegesis Al-Burhan fi Hall Mushkilat al-Qur’an. The study focuses on how the author utilizes linguistic, morphological, and grammatical principles to clarify complex Qur’anic expressions and resolve interpretive difficulties. Maulana Rustami’s approach demonstrates his profound command over Arabic lexicon and grammar, reflecting a scholarly synthesis of classical linguistic heritage and exegetical depth.Through detailed lexical explanation, etymological analysis, and contextual interpretation, he succeeds in unveiling the semantic richness of Qur’anic vocabulary. His methodology combines precision of language with clarity of thought, making his tafsir both accessible and academically valuable. This analytical review concludes that Al-Burhan fi Hall Mushkilat al-Qur’an serves as an important contribution to Qur’anic linguistic studies, representing a model of balanced integration between linguistic scholarship and theological insight.